Effect of α Subunit on Allosteric Modulation of Ion Channel Function in Stably Expressed Human Recombinant γ-Aminobutyric AcidA Receptors Determined Using 36Cl Ion Flux - Smith, Alison J.; Alder, Luanda; Silk, Jonathan; Adkins, Charles; Fletcher, Alan E.; Scales, Tim; Kerby, Julie; Marshall, George; Wafford, Keith A.; McKernan, Ruth M.; Atack, John R. (Molecular pharmacology, 2001)
Inhibitory γ-aminobutyric acid (GABA)A receptors are subject to modulation at a variety of allosteric sites, with pharmacology dependent on receptor subunit combination. The influence of different α subunits in combination with β3γ2s was examined in stably expressed human recombinant GABAA receptors by measuring 36Cl influx through the ion channel pore. Muscimol and GABA exhibited similar maximal efficacy at each receptor subtype, although muscimol was more potent, with responses blocked by picrotoxin and bicuculline. Receptors containing the α3 subunit exhibited slightly lower potency. The comparative pharmacology of a range of benzodiazepine site ligands was examined, revealing a range of intrinsic efficacies at different receptor subtypes. Of the diazepam-sensitive GABAA receptors (α1, α2, α3, α5), α5 showed the most divergence, being discriminated by zolpidem in terms of very low affinity, and CL218,872 and CGS9895 with different efficacies. Benzodiazepine potentiation at α3β3γ2s with nonselective agonist chlordiazepoxide was greater than at α1, α2, or α5 (P < 0.001). The presence of an α4 subunit conferred a unique pharmacological profile. The partial agonist bretazenil was the most efficacious benzodiazepine, despite lower α4 affinity, and FG8205 displayed similar efficacy. Most striking were the lack of affinity/efficacy for classical benzodiazepines and the relatively high efficacy of Ro15-1788 (53 ± 12%), CGS8216 (56 ± 6%), CGS9895 (65 ± 6%), and the weak partial inverse agonist Ro15-4513 (87 ± 5%). Each receptor subtype was modulated by pentobarbital, loreclezole, and 5α-pregnan-3α-ol-20-one, but the type of α subunit influenced the level of potentiation. The maximal pentobarbital response was significantly greater at α4β3γ2s (226 ± 10% increase in the EC20 response to GABA) than any other modulator. The rank order of potentiation for pregnanolone was α5 >α2 >α3 = α4 >α1, for loreclezole α1 = α2 = α3 >α5 >α4, and for pentobarbital α4 = α5 = α2 >α1 = α3.